Co Relation of Thyroid Function Test with the Clinical Presentation (Medical Forum Monthly, 2024)
Objective: To correlate the biochemical thyroid profile with the clinical presentation of the patient and decision about the time of surgery. Study Design: It is an analytical cross sectional study. Place & Duration of Study: This study was carried out in the Department of Surgery, Fauji Foundation Hospital, Rawalpindi from 1st January 2010 to 31st March 2011 Patients & Methods: Thirty patients were included in this study after taking consent & approval from the ethical committee of the hospital. All of them were females. Age ranges between 13 to 45 with mean of 22.26 years. These patients presented with a swelling in front of neck with or without signs of hypothyroidism or hyperthyroidism. Trial of 6 to 12 months given to every patient to bring the TFT’s within normal range. Only those patients were included in the study who took the medicines regularly. Mode of presentation was out door department of Fauji Foundation Hospital Rawalpindi. Patients were examined clinically by surgeon and anesthetist for risk assessment. Routine laboratory investigations including thyroid function test were requested and analyzed by operating surgeon. TFT’s were co-related with the clinical signs and symptoms of the patients. Patients were divided into two groups. Group one includes clinically euthyroid patients with TFT’s within normal range. Group two again include clinically euthyroid patients but abnormal TFT’s. Results: A total of 30 patients were included in this study. All of them were females & clinically euthyroid. Mode of presentation was the outdoor patient department of Fauji Foundation hospital. Presenting complaint was swelling in front of neck. 23 out of 30 patients (66.6 %) had normal TFT’s & clinically euthyroid. 7 out of 30 Patients (33.3%) shows variation between their thyroid profile and clinical presentation. Sub or near total thyroidectomy was done in all the patients. Recovery was un-eventful. Conclusion: Operation on thyroid gland is a major undertaking & decision should be taken by senior surgeon. Ideally TFT’s should be within normal range as well as patient should be euthyroid clinically in order to avoid post operative complications. In those cases where patient is clinically euthyroid but biochemically status is either hyper or hypo thyroid, surgery can be done after clinical trial of at least six months with thyroxin or anti thyroid drugs with a view to bring the TFT’s within normal range. We can conclude that although the biochemical profile of the patients with thyroid disease is important but in country like Pakistan where thyroid hormonal assay is not easily available the surgery can be done by careful clinical assessment, keeping in view compliance of patient, regularity of taking medicine, clinical status & side effects of medical treatment.